CORRELATION BETWEEN QUALITY OF LIFE AND OSTEOLYSIS AROUND LUMBAR PEDICLE SCREWS - RISSO NETO,MARCELO ITALO (2016)
ABSTRACT Objective: To evaluate whether the presence of osteolysis around the pedicle screws affects the quality of life of patients who underwent posterolateral arthrodesis of the lumbosacral spine. Methods: A retrospective study of patients undergoing lumbar posterolateral or lumbosacral arthrodesis due to spinal degenerative disease. CT scans of the operated segments were performed at intervals of 45, 90, 180, and 360 postoperatively. In these tests, the presence of a peri-implant radiolucent halo was investigated, which was considered present when greater than 1mm in the coronal section. Concurrently with the completion of CT scans, the participants completed the questionnaire Oswestry Disability Index (ODI) to assess the degree of disability of the patients. Results: A total of 38 patients were evaluated, and 14 (36.84%) of them showed some degree of osteolysis around at least one pedicle screw at the end of follow-up. Of the 242 analyzed screws, 27 (11.15%) had osteolysis in the CT coronal section, with the majority of these occurrences located at the most distal level segment of the arthrodesis. There was no correlation between the presence of the osteolysis to the quality of life of patients. The quality of life has significantly improved when comparing the preoperative results with the postoperative results at different times of application of ODI. This improvement in ODI maintains linearity over time. Conclusion: There is no correlation between the presence of peri-implant osteolysis to the quality of life of patients undergoing lumbar or posterolateral lumbosacral arthrodesis in the follow-up period up to 360 days. The quality of life in postoperative has significantly improvement when compared to the preoperative period.